2020
DOI: 10.17058/jeic.v10i2.14027
|View full text |Cite
|
Sign up to set email alerts
|

Bactérias associadas a formigas coletadas em hospitais em Anápolis – GO

Abstract: Justificativa e Objetivos: os hospitais são locais propícios para a instalação e propagação de insetos, especialmente formigas. Essas, além da sua capacidade adaptativa, vivem em mutualismo com outros animais, como fungos e bactérias, o que confere risco elevado para infecções nosocomiais. O presente estudo teve como objetivo identificar a microbiota bacteriana associada com formigas intra-hospitalares na cidade de Anápolis, Goiás, e discutir o papel de tais agentes no desenvolvim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The wards and critical care units are often with overload of severe COVID-19 cases, a predisposing condition to development of hospital acquired infectious complications. Besides the usual concerns in this setting, one should consider unsuspected interactions of insects with diverse pathogenic microorganisms in the hospital environment (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The wards and critical care units are often with overload of severe COVID-19 cases, a predisposing condition to development of hospital acquired infectious complications. Besides the usual concerns in this setting, one should consider unsuspected interactions of insects with diverse pathogenic microorganisms in the hospital environment (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…A research done in two hospitals of Anápolis-GO, Brazil showed that Staphylococcus spp., Gram-positive bacilli, Klebsiella ozaenae, K. rhinoscleromatis, E coli spp., and Yersinia pseudotuberculosis were carried by T. melanocephalum and P. longicornis (6). Ants were captured at wards, intensive/semiintensive care units, and nutrition sectors, and Staphylococcus spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation